2017
DOI: 10.3892/ol.2017.6927
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory network involving miRNAs and genes in serous ovarian carcinoma

Abstract: Abstract. Serous ovarian carcinoma (SOC) is one of the most life-threatening types of gynecological malignancy, but the pathogenesis of SOC remains unknown. Previous studies have indicated that differentially expressed genes and microRNAs (miRNAs) serve important functions in SOC. However, genes and miRNAs are identified in a disperse form, and limited information is known about the regulatory association between miRNAs and genes in SOC. In the present study, three regulatory networks were hierarchically const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 79 publications
0
1
0
Order By: Relevance
“…MicroRNAs (miRNAs/miRs) have several target genes and extensively participate in the gene regulatory network to exert various biological effects. Research suggests that miRNAs are key regulatory factors of the downstream network, to a greater extent than other regulatory factors and/or ligands ( 19 ). Previous work has indicated that miRNAs are key in the regulation of bone functional cell apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNAs (miRNAs/miRs) have several target genes and extensively participate in the gene regulatory network to exert various biological effects. Research suggests that miRNAs are key regulatory factors of the downstream network, to a greater extent than other regulatory factors and/or ligands ( 19 ). Previous work has indicated that miRNAs are key in the regulation of bone functional cell apoptosis.…”
Section: Introductionmentioning
confidence: 99%